The Increase in Love-Peace Character Education Through Teaching Hadits Memorization in 5-6 Year-Old Children - Hafriani, Rizka (JURNAL BUNGA RAMPAI USIA EMAS, 2017)
The objective of this research was to find out the demand for education of love-peace character  in 5-6 year-old children through the teaching of hadits memorization at Raudhatul Athfal (RA) Ar-Rasyid, Sukamaju Village, Sunggal Subdistrict, Deli Serdang Regency, North Sumatera. The research used class teaching action with descriptive method. The research subjects were a teacher and 20 group B students. The data were gathered by conducting observation and data analysis. The result of the study showed that the teaching planning for increasing love-peace character education through the activity of hadits memorization was categorized as successful; its implementation was considered successful, and its result was also very good since every aspect of love-peace character education highly increased.